Buy to let: Investment buyers in a housing search model - Erlend Eide Bø (Statistics Norway, Research Department, 2019)
In this paper, I explore and explain how buy-to-let investors affect housing price dynamics. The impact of buy-to-let investors on the housing market is much discussed by policy makers, but previously not considered in the literature. I develop a structural search model that allows housing owners to buy second houses to let out, and let rents be determined endogenously. To motivate the model, I present empirical evidence from the city of Oslo showing that a significant share of buyers are buy-to-let investors, and both rents and the share of second house buyers are positively correlated with housing prices. The model introduces two mechanisms that affect volatility compared to a model with no landlords and constant rents. First, the endogenous correlation of rents and housing prices makes it attractive for non-owners to buy in "hot" markets, to avoid paying high rents. Second, the increased incentives to become landlords in high rent periods further increase the number of buyers and amplify the effect of high rents on housing prices and transaction volumes. The model is calibrated using data from Oslo, and is able to match quantitatively the high investor share and housing price volatility of a housing boom.
Keywords: D83; R21; R31; 330; Housing; Search; Rental market